The Influence of Participation in Pregnancy Courses and Breastfeeding Support Groups on Attitudes and Knowledge of Health Professionals about Breastfeeding - Marija Čatipović; Zrinka Puharić (MDPI AG, 2023)
Numerous factors affect the behavior, attitudes, and knowledge of health professionals about breastfeeding. The aim of this paper is to determine the impact of participation in pregnancy courses and breastfeeding support groups on the attitudes and knowledge of health professionals about breastfeeding. The study compares two groups of health professionals according to the results they achieved on a validated questionnaire of behavior, attitudes, and knowledge about breastfeeding. The authors did not make personal contact with the respondents, as the questionnaires were filled out online. The two groups of respondents differed according to the frequency of participation in pregnancy courses, that is, groups for breastfeeding support. The results are presented tabularly and graphically (frequencies and percentages), while differences in the results between the infrequent and regular participants are shown with the Mann-Whitney U test (asymmetric distribution). Better results on the questionnaire were achieved by those who regularly attended breastfeeding support groups (Mdn = 149, IQR = 11) in comparison to infrequent visitors (Mdn = 137, IQR = 23). The same is found for regular visitors of pregnancy courses (Mdn = 149, IQR = 15.75) in comparison to infrequent visitors (Mdn = 137, IQR = 23). The differences are statistically significant (p < 0.00). Partial correlation confirms a more significant influence of breastfeeding support groups (<0.00) than pregnancy courses (p = 0.34). Working in breastfeeding support groups had a statistically significant positive effect on the attitudes and knowledge of health professionals about breastfeeding. The topic of breastfeeding should be given more space and importance during pregnancy courses as well. Personal experience working in breastfeeding support groups and pregnancy courses should be incorporated into the training of medical students.